Implementation of Teacher Certification Policy in SMA Negeri 1 Tondano of Minahasa Regency - Tumundo, Syiulce Hanna; Mokat, Jetty E. H.; Tumbel, Goinpeace H. (Technium Social Sciences Journal, 2024)
This research aims to find out, describe and analyze why certified teachers do not have the competencies expected to improve the academic abilities of students. This study uses a qualitative method. Based on the results of data analysis, a number of findings were obtained as follows: (1) Pedagogical competence of teachers who have understood the basic rules regarding professional education have not fully utilized the capacity development forums that have been provided. To understand students, teachers still have a tendency to focus on certain students, for example students who excel and students who have problems. Meanwhile, students who have moderate or intermediate abilities are often ignored. To create an attractive teaching and learning process, certified senior teachers need to improve their ability to use technological tools and mastery of ICT in accordance with existing technological developments and advances, and the availability of technology-based facilities or infrastructure needs to be improved. (2) Personality Competence: There are some professionally certified teachers at SMA Negeri 1 Tondano who have not been able to be role models for their students because of the lack of discipline on the part of the teachers, which ultimately makes the teachers lose their authority. Teacher indiscipline also ultimately means teachers are unable to evaluate their self-performance objectively. (3) Social Competence teachers who should be role models in interacting and communicating have not been able to implement good communication practices, even though they establish good relationships between all elements of the school. Communication that is not polite indicates that the teacher does not have the ability and skills to interact and communicate. Nevertheless, a positive educational environment has been created in SMA Negeri 1 Tondano because all elements behave well, avoid problems, respect and appreciate each other, and help each other. (4) Professional Competence has not been reflected in the teachers of SMA Negeri 1 Tondano, because the teachers still lack discipline, both in terms of working hours and dress discipline. Monitoring of the learning process has been carried out by the school and related agencies, but violations are still found by teachers. The implementation of coaching sanctions and reducing teaching hours apparently did not deter teachers.